Incidence and Timing of Cancer in HIV-Infected Individuals Following Initiation of Combination Antiretroviral Therapy - Yanik, Elizabeth L. (Oxford University Press, 2013)
BACKGROUND: Cancer is an important cause of morbidity and mortality in individuals infected with human immunodeficiency virus (HIV), but patterns of cancer incidence after combination antiretroviral therapy (ART) initiation remain poorly characterized. METHODS: We evaluated the incidence and timing of cancer diagnoses among patients initiating ART between 1996 and 2011 in a collaboration of 8 US clinical HIV cohorts. Poisson regression was used to estimate incidence rates. Cox regression was used to identify demographic and clinical characteristics associated with cancer incidence after ART initiation. RESULTS: At initiation of first combination ART among 11 485 patients, median year was 2004 (interquartile range [IQR], 2000–2007) and median CD4 count was 202 cells/mm(3) (IQR, 61–338). Incidence rates for Kaposi sarcoma (KS) and lymphomas were highest in the first 6 months after ART initiation (P < .001) and plateaued thereafter, while incidence rates for all other cancers combined increased from 416 to 615 cases per 100 000 person-years from 1 to 10 years after ART initiation (average 7% increase per year; 95% confidence interval, 2%–13%). Lower CD4 count at ART initiation was associated with greater risk of KS, lymphoma, and human papillomavirus–related cancer. Calendar year of ART initiation was not associated with cancer incidence. CONCLUSIONS: KS and lymphoma rates were highest immediately following ART initiation, particularly among patients with low CD4 cell counts, whereas other cancers increased with time on ART, likely reflecting increased cancer risk with aging. Our results underscore recommendations for earlier HIV diagnosis followed by prompt ART initiation along with ongoing aggressive cancer screening and prevention efforts throughout the course of HIV care.